2015
DOI: 10.1037/ser0000019
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptation, psychometric properties, and outcomes of the Native American Spirituality Scale.

Abstract: Spirituality is central to many Native Americans (NAs) and has been associated with recovery from substance use disorders (SUDs). However, no published questionnaire uniquely taps tribal-specific spiritual beliefs and practices. This hinders efforts to integrate traditional NA spirituality into SUD treatment and track spiritual outcomes. As part of a randomized controlled trial examining SUD treatment for NAs, we adapted the Daily Spiritual Experience Scale (DSES) in collaboration with members of a Southwest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
(51 reference statements)
1
21
0
1
Order By: Relevance
“…Therefore, we cannot assume these findings will generalize to other members of the community or to other Native communities or cultures. However, as many of the findings from this study (e.g., the importance of spirituality among AI/ANs; Greenfield et al., ) have been reported previously in the literature, we are confident that the findings do accurately represent the perspectives of many community members and contend that this research constituted a necessary and valuable first step toward our current intervention development work and future research endeavors.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, we cannot assume these findings will generalize to other members of the community or to other Native communities or cultures. However, as many of the findings from this study (e.g., the importance of spirituality among AI/ANs; Greenfield et al., ) have been reported previously in the literature, we are confident that the findings do accurately represent the perspectives of many community members and contend that this research constituted a necessary and valuable first step toward our current intervention development work and future research endeavors.…”
Section: Discussionsupporting
confidence: 75%
“…Participants’ responses, however, may have been shaped by the manner in which the questions were delivered. For example, AI/AN participants might not have assumed that questions about “religious or spiritual services,” which may have connoted attending church or synagogue services, were inclusive of Native religious ceremonies or spiritual events (see Greenfield et al, 2015). Most measures of religiosity and spirituality, including the one used in the current study, have not been validated for use with AI/ANs, and culturally-adapted assessment of these constructs for AI/ANs has been indicated (Greenfield et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Further, prior research has indicated that many urban AI/ANs are interested in Native religious and spiritual practices but are unable to access them (Clifasefi, Collins, Torres, Grazioli, & Mackelprang, 2016; Hartmann & Gone, 2012). Considering that religious and spiritual practices have a protective effect in the general population (Greenfield et al, 2015), we recommend that researchers and providers assess the importance and potential clinical significance of Native practices and, when appropriate, help to connect AI/ANs with opportunities to engage in them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary outcomes included percent of days abstinent from alcohol, marijuana, and all drugs via self‐report and an oral swab drug screen; spirituality was also measured over time. Pilot outcomes ( N = 8) at 8‐month follow‐up yielded medium effect sizes for improvements in percent of days abstinent for alcohol, marijuana, and all drugs, as well as reductions in psychological distress (Venner et al., ) and increased spiritual behaviors and beliefs (Greenfield et al., ). Analyses of RCT data comparing MICRA to treatment‐as‐usual are underway.…”
Section: Community Settingsmentioning
confidence: 99%